Calculation & simulation of electric-based fractionation methods for separation of airborne particles - Lee, Jun Hong (Nanyang Technological University, 2023)
The particulate matter present in the air can have significant negative impacts on human health, causing respiratory and cardiovascular problems. However, conventional methods of air filtration lack the ability to distinguish particle size, which can further exacerbate the issue.